EQUALITY RIGHTS: AN ANALYSIS - Grey, Julius (Revue de droit de l'Université de Sherbrooke, 1988)
This article seeks to analyse the notion of equality which is so important in present-day Canada and to consider its legal, historical and moral roots. In particular, it attempts to examine the types of equality desirable for different functions: legal equality, equality of opportunity and equality of results. It considers the forbidden types of discrimination in the light of recent jurisprudence. Finally it debates the issue of the "individual" as opposed to the "collective" nature of equality rights. It proposes an "individualistic" answer which, while it rejects most affirmative action and most forms of group rights in democratic society, is yet javourable to the welfare state and to state-induced social justice.